The Effect of Video Content and the Use of Hashtags on Instagram Social Media on the Formation of Zozo Garden Brand Image in Bandar Lampung - Sabarina, Adinda Syahda Alya; Yusendra, M. Ariza Eka (Prosiding International conference on Information Technology and Business (ICITB), 2023)
The purpose of this study is to explore whether video content and the hashtag #ZozoGakMahalLagi are able to help Zozo Garden to create an affordable Brand Image for its niche target market so that it can increase their competitiveness among the fierce competition of the cafe / restaurant business in Bandar Lampung. This type of research is causality exploratory quantitative research, with the population followers of the @zozo.garden Instagram account of 25,100 followers and the sample to be studied as many as 100 respondents. The analytical tool used is Multiple regression analysis obtained with the help of SPSS to determine whether there is a positive causality relationship between Video Content and Hashtag Determination on the Development of the new Zozo Garden Brand Image.Keywords-digital marketing, brand image, Social media marketing, instagram, hashtag management